In Hoc Signo Vinces: The Politics of Religion as a Source of Power and Conflict - Doja, Albert (Politics, religion & ideology, 2019)
In this article, I explore the importance and passion for historical reconstructions by means of media events and public representations. To this aims, among other illustrative examples, I take issue with the celebrations to mark the legacy of Emperor Constantine to Christianity among Southeast European peoples, including Albanians. Similar celebrations are often used and misused to forward or contest various claims to immutable ethnic belonging and religious tolerance. They always support negotiating or challenging ethno-political agendas. They may show the ways in which historical, cultural and religious heritage is entangled in identity politics, which could provide new insights to a better understanding of the politics of religion in international affairs and everyday life in the Balkans.